2022
DOI: 10.3390/agronomy12040840
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Year Field Experiment for the Integrated Management of Bread and Durum Wheat Fungal Diseases and of Deoxynivalenol Accumulation in the Grain in Central Italy

Abstract: A two-year (2018/19 and 2019/20) field experiment was carried out to evaluate the efficacy of recently developed fungicide combinations (with different modes of action) towards fungal diseases on seven bread and eight durum wheat varieties. The trial was performed at the FIELDLAB experimental station of the University of Perugia (Italy). The diseases were assessed under natural pressure except for Fusarium head blight (FHB) for which artificial inoculation with a Fusarium culmorum deoxynivalenol (DON)-producin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 68 publications
1
3
0
Order By: Relevance
“…In this context, we can associate the higher DON accumulation with the increased protein content in wheat seeds. The same pattern was reported by other researchers [ 65 , 66 ] in recent studies. They observed that the protein content increased in the presence of Fusarium artificial inoculation.…”
Section: Discussionsupporting
confidence: 92%
“…In this context, we can associate the higher DON accumulation with the increased protein content in wheat seeds. The same pattern was reported by other researchers [ 65 , 66 ] in recent studies. They observed that the protein content increased in the presence of Fusarium artificial inoculation.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Krnjaja et al (2015) found that DON levels in bread wheat kernels were significantly affected by the cultivars. Balducci et al (2022) have established the strongest positive correlation between FHB symptoms and DON levels in durum wheat during the wetter growing season. However, in our study, the relationship between F. graminearum incidence and DON level was not positively correlated.…”
Section: Discussionmentioning
confidence: 90%
“…Thus, resistance to FHB also includes resistance to DON (Scala et al, 2016). The best timing for fungicide application during the flowering wheat stage has a crucial role in reducing FHB and DON contamination in conducive climatic conditions (Balducci et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Monastir was chosen because it is a modern durum wheat cultivar extensively cultivated around the Mediterranean basin [ 58 ] and it is reported to be a cultivar with medium susceptibility to salinity stress [ 24 ].…”
Section: Methodsmentioning
confidence: 99%